Time won't heal - Abd Razak, Dzulkifli (2005)
TEN years ago, a group of Serb paramilitary soldiers, dubbed the "Scorpions", shocked the world when they butchered Bosnians at Srebrenica, in eastern Bosnia. Early last month, the world was again shocked when video recording of that chilling tragedy in July 1995 was released. Described by the media as "sickening", it showed a "brutal, callous and disgraceful crime against civilians", to use the words of the Serbian Prime Minister. On his orders, eight suspects were arrested. The video was made available during the war trial of the former Serbian strongman, Slobodan Milosevic, in The Hague. It was the first graphic material on the massacre unearthed by a Serbian human rights organisation.